Pemberdayaan Masyarakat Lokal: melalui Pelatihan Pembuatan Komposter dan Dampaknya untuk Ekowisata Berkelanjutan di Pamboborang - Futri Adriana Aksar; Virda Eviyanti Deril; Sri Apriani Puji Lestari; Nur Okviyani; Sarmila Sarmila (Politeknik Negeri Cilacap, 2026)
Organik waste management is a major challenge in developing ecotourism in Pamboborang Village, Majene Regency, West Sulawesi. This community service activity aimed to empower the local community, particularly the blacksmith group, through training in simple composter construction to support sustainable organik waste management. The applied methods included a one-day intensive workshop, one-month post-training mentoring, and pre-test and post-test evaluations using structured questionnaires. The training involved constructing composters using two lidded buckets, perforated PVC pipes, and a leachate tap. The results indicated a 70% increase in participants’ knowledge, with the highest improvement (40%) in technical aspects of composter making. Post-training monitoring showed that 80% of participants continued to use the composters after three months. This activity provided environmental benefits through a 40% reduction in organik waste and socio-economic benefits by increasing awareness of cleanliness and promoting compost utilization for local agriculture. The novelty of this program lies in its integration of technical training with a community-based mentoring system, which enhances the sustainability of ecotourism development in Pamboborang.